Effects of elevated CO2 and decreased water availability on holm-oak seedlings in controlled environment chambers - López, B; Sabate, S; Ruiz, I; Gracia, C (IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS, 1998)
In Mediterranean ecosystems, water is an important limiting factor for plant growth. In addition to the increase in atmospheric CO2, some models predict increased drought in Mediterranean areas as a consequence of global change. Thus, to determine how increased atmospheric CO2 interacts with increased water stress and affects Mediterranean plant growth is an important achievement. The present study analyses how helm oak (Quercus ilex L.) seedlings are affected by both elevated CO2 and increased water stress. The CO2 concentrations were supplied in controlled environment chambers (350 and 500 ppm CO2), and water stress was performed according to a Mediterranean pattern (Potential Evapotranspiration to Rainfall ratio). The increased water stress was attained by watering half of the Mediterranean reference pattern. Results show that the positive effects of elevated CO2 on photosynthesis and growth are counteracted by increased water stress.
Keywords: CO2; controlled environment chambers; Quercus ilex